Progress in biomaterials inspired by the extracellular matrix - Zhuolin Chen; Chengcheng Du; Senrui Liu; Jiacheng Liu; Yaji Yang; Lili Dong; Weikang Zhao; Wei Huang; Yiting Lei (Giant, 2024)
Inspired by the extracellular matrix (ECM), biomaterials have emerged as promising strategies in the biomedical research and engineering domain, offering unique characteristics for tissue regeneration, drug delivery, therapeutic interventions, and cellular investigations. The ECM, a dynamic network structure secreted by various cells, primarily comprises diverse proteins capable of facilitating tissue-ECM signaling and regulatory functions through its rich array of bioactive substances and multi-level structural properties. Drawing inspiration from the intricate structure and biochemical composition of natural ECM, researchers have developed various biomaterials to encapsulate these features and create biomimetic microenvironments, such as electrospinning, hydrogels/hydrogel microspheres, decellularized ECM(dECM), and ECM-mimicking peptides. Furthermore, by mimicking the structural composition of ECM components, ECM-inspired biomaterials exhibit varying degrees of ECM functionalization, including providing structural support, cell adhesion, signal transduction, mitigating immune responses, and tissue remodeling. In summary, the advancements in ECM-inspired biomaterials offer significant promise in addressing key challenges in the fields of tissue engineering, regenerative medicine, and drug delivery.